Driving Employee Performance: The Impact of Achievement Motivation and Culture at a Logistics SOE - Alfilail Taftajani; Bulan Tati Fitria; Boy Suzanto; Dhea Perdana Coenraad (P3M, STIE Pasundan, Bandung, Indonesia., 2026)
Suboptimal employee performance severely challenges organizational efficiency, especially within competitive public sectors. This study addresses the performance gaps currently hindering a state-owned shipping enterprise in Bandung, Indonesia. This research investigates how achievement motivation and organizational culture influence employee performance within the state-owned logistics sector. The study employs a quantitative, descriptive, and verficiative research design. Utilizing a survey approach, we collected primary data from a sample of 100 employees selected through simple random sampling. The data analysis utilizes path analysis to evaluate the direct effects and statistical significance of the variables. The statistical analysis reveals that both achievement motivation and organizational culture significantly boost employee performance, with corporate culture acting as the primary driver. The results confirm that strategic interventions in workplace dynamics directly elevate workforce productivity. Unlike generic organizational behavior studies, this research provides unique empirical evidence by focusing specifically on a state-owned shipping and logistics enterprise in a developing economy. It uncovers how civil service mindsets shift when coupled with targeted achievement-driven incentives. These findings imply that state-owned logistics managers must actively cultivate a high-achievement culture and modernize organizational values. Practically, implementing robust reward systems and alignment programs will directly resolve the current performance deficits.